A Good Position for Birth : Pregnancy, Risk, and Development in Southern Belize - Maraësa, Aminata (Book collections on Project MUSE., 2018)
"This book provides an ethnographically rich analysis of pregnancy and birth in southern Belize at the intersection of local public health initiatives, transnational development projects, and the culturally influenced beliefs and behaviors of pregnant women. Herein lie the stories of real women and their caregivers that call attention to local understandings of gender, the provision of healthcare services, competing assessments of maternal risk, and an at-times precarious natural environment to illuminate the lived reproductive realities of women in southern Belize within the faceless statistical categories of maternal health."--